Direct Crosstalk Between Cancer and Osteoblast Lineage Cells Fuels Metastatic Growth in Bone via Auto‐Amplification of IL‐6 and RANKL Signaling Pathways. (September 2014) - Zheng, Yu; Chow, Shu‐Oi; Boernert, Katja; Basel, Dennis; Mikuscheva, Anastasia; Kim, Sarah; Fong‐Yee, Colette; Trivedi, Trupti; Buttgereit, Frank; Sutherland, Robert L; Dunstan, Colin R; Zhou, Hong; et al.
ABSTRACT The bone microenvironment and its modification by cancer and host cell interactions is a key driver of skeletal metastatic growth. Interleukin‐6 (IL‐6) stimulates receptor activator of NF‐κB ligand (RANKL) expression in bone cells, and serum IL‐6 levels are associated with poor clinical outcomes in cancer patients. We investigated the effects of RANKL on cancer cells and the role of tumor‐derived IL‐6 within the bone microenvironment. Using human breast cancer cell lines to induce tumors in the bone of immune‐deficient mice, we first determined whether RANKL released by cells of the osteoblast lineage directly promotes IL‐6 expression by cancer cells in vitro and in vivo. We then disrupted of IL‐6 signaling in vivo either via knockdown of IL‐6 in tumor cells or through treatment with specific anti‐human or anti‐mouse IL‐6 receptor antibodies to investigate the tumor effect. Finally, we tested the effect of RANK knockdown in cancer cells on cancer growth. We demonstrate that osteoblast lineage‐derived RANKL upregulates secretion of IL‐6 by breast cancers in vivo and in vitro. IL‐6, in turn, induces expression of RANK by cancer cells, which sensitizes the tumor to RANKL and significantly enhances cancer IL‐6 release. Disruption in vivo of this auto‐amplifying crosstalk by knockdown of IL‐6 or RANK in cancer cells, or via treatment with anti‐IL‐6 receptor antibodies, significantly reduces tumor growth in bone but not in soft tissues. RANKL and IL‐6 mediate direct paracrine‐autocrine signaling between cells of the osteoblast lineage and cancer cells, significantly enhancing the growth of metastatic breast cancers within bone. © 2014 American Society for Bone and Mineral Research.